1993
DOI: 10.1111/j.1469-8137.1993.tb04536.x
|View full text |Cite
|
Sign up to set email alerts
|

Mustards, mustard oils and mycorrhizas

Abstract: Intact, living roots of Brassica kaber (DC.) Wheeler and Brassica nigra. L. (Brassicaceae) were inhibitory to the germination of spores of the mycorrhizal fungi Glomus intraradices Schenck & Smith and Glomus etunicatum Becker & Gerd. Roots from two similarly non-mycotrophic species, spinach (Chenopodiaceae) and Amaranthus retroflexus L. (Amaranthaceae), had no effect on the germination of spores of G. intraradices. The roots of two out of three mycotrophic species examined were stimulatory to germination of G.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(54 citation statements)
references
References 16 publications
2
52
0
Order By: Relevance
“…Measures of sinigrin content in the leaves of the field grown plants confirmed that the two selection lines maintained their differences in sinigrin expression in the field conditions (Lankau & Strauss 2007). While the toxic properties of glucosinolate breakdown products are well documented (Schreiner & Koide 1993;Kliebenstein 2004), the proximate mechanism by which the genetic differences in sinigrin expression in leaves caused the observed changes in soil microbial communities is not clear from this research. Sinigrin could have leached from leaves or litter, or leaf sinigrin levels could be genetically correlated with root sinigrin levels or some other unmeasured trait.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Measures of sinigrin content in the leaves of the field grown plants confirmed that the two selection lines maintained their differences in sinigrin expression in the field conditions (Lankau & Strauss 2007). While the toxic properties of glucosinolate breakdown products are well documented (Schreiner & Koide 1993;Kliebenstein 2004), the proximate mechanism by which the genetic differences in sinigrin expression in leaves caused the observed changes in soil microbial communities is not clear from this research. Sinigrin could have leached from leaves or litter, or leaf sinigrin levels could be genetically correlated with root sinigrin levels or some other unmeasured trait.…”
Section: Discussionmentioning
confidence: 62%
“…We used three other annual species (Amsinckia menziesii, Sonchus oleraceus, and Malva parviflora) as heterospecific competitors; all three commonly co-occur with B. nigra and form connections with AMF (observed and documented below). Brassica nigra, like most members of the Brassicaceae, does not form AMF associations (Schreiner & Koide 1993).…”
Section: S T U D Y S P E C I E Smentioning
confidence: 99%
See 1 more Smart Citation
“…We measure effective production of the exogenous glucosinolate in root tissues of A. thaliana CYP79A1 (Choesin and Boerner 1991) and mustard roots (Schreiner and Koide 1993) and directly impact microbe living on roots. Populations closely associated with plant roots directly exposed to these compounds but also rhizospheric populations are impacted by this glucosinolate profile change.…”
Section: Discussionmentioning
confidence: 99%
“…These allelochemicals appear to act as "novel weapons" sensu Callaway and Ridenhour (25), because they are more toxic to AMF strains from North America (introduced range) versus Europe (native range) (38). A. petiolata, like all members of the Brassicaceae, does not form mycorrhizal connections (40). Tissue concentrations of sinigrin, one of the major allelochemicals of A. petiolata, have evolved rapidly during this invasion, with higher sinigrin concentrations in populations on the expanding range edge compared with older populations (41).…”
mentioning
confidence: 99%